The implementation of an automated system reduces the time of attention in the processes applicable to the single window of tourism in the Provincial Municipality of Callao - Farfán Jiménez, Junior Andrés (2020)
The objective of this study is present the guidelines to develop the implementation of an Automated System in order to reduce service times in the processes applicable to the Single Window of Tourism in the Provincial Municipality of Callao, based on the development of Management by Processes. It presents the steps to follow to achieve the implementation of an Automated System and the example is shown in which it was possible to verify that said implementation reduces the attention times in the Provincial Municipality of Callao. With the implementation of an Automated System everyone wins: first, the workers, since they will be able to carry out their tasks in the shortest time and minimize unforced errors; secondly, the Municipality, since it will offer automated and simplified services, and finally the clients, because the costs of administrative procedures will be reduced and because there is a new approach to modernize Public Entities.